2004
DOI: 10.1038/sj.jhh.1001742
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-glutamyltransferase: an effect modifier in the association between age and hypertension in a 4-year follow-up study

Abstract: We performed a prospective study to assess whether the relationship of age with hypertension was stronger in men with high normal serum gamma glutamyltransferase (GGT) than in those with lower GGT levels. The study population included 8170 healthy male workers in a steel manufacturing company who had undergone health examinations in both 1994 and 1998. The higher the baseline GGT level, the effect of age on the development of hypertension was stronger. The incidence of hypertension among those aged 25-34, 35-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 18 publications
(42 reference statements)
3
12
1
Order By: Relevance
“…14 -16,23-25 Several studies proposed that ␥-glutamyltransferase may be a marker of oxidative stress, or perhaps it is involved in the generation of reactive oxygen species. 16,25,26 However, in our results, the serum aminotransferase level was associated only with ICH, but not with ischemic heart disease or ischemic stroke. This, a specific association with ICH cannot be fully explained by oxidative stress.…”
Section: Possible Mechanismscontrasting
confidence: 54%
“…14 -16,23-25 Several studies proposed that ␥-glutamyltransferase may be a marker of oxidative stress, or perhaps it is involved in the generation of reactive oxygen species. 16,25,26 However, in our results, the serum aminotransferase level was associated only with ICH, but not with ischemic heart disease or ischemic stroke. This, a specific association with ICH cannot be fully explained by oxidative stress.…”
Section: Possible Mechanismscontrasting
confidence: 54%
“…It has been shown that the higher the baseline GGT level, the stronger the effect of age on the development of hypertension 27) ; thus, the well-described association between serum GGT and blood pressure might not be significant in women. Furthermore, serum GGT has also been shown to be more associated with hypertriglyceridemia and abnormal glucose tolerance among components of MetS, suggesting that serum GGT has a closer relationship with hepatic insulin resistance 13,28) .…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] A recent prospective study has confirmed a positive association between age, serum gGT and the subsequent risk of hypertension. 26 This relationship between gGT and hypertension may be independent of alcohol consumption, where gGT has been shown to correlate with systolic and diastolic blood pressure (Table 3). 27 The reasons for these associations have been poorly understood; although alcohol consumption may be relevant, the causal link in many individuals between liver disease and hypertension seems to be the metabolic syndrome (Figure 1).…”
Section: Hypertension Metabolic Syndrome and Fatty Livermentioning
confidence: 99%